2019
DOI: 10.29328/journal.jsmt.1001047
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric characteristics and somatotype of professional soccer players by position

Abstract: Some studies conclude that there is a close relation between the anthropometric and the physiologic characteristics of the player and its ability to play football at a certain level [1,5,6]; such characteristics are decisive for an optimal physical level and therefore a good level in the game [4,7,8].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
0
5
0
3
Order By: Relevance
“…Measurements of individuals’ linear dimensions, body diameters, body mass, and skinfolds, which are considered the key components of the somatic build profile of an elite player, have been monitored [ 6 , 9 ]. These measurements are critical in selecting players for each position on the court [ 10 , 11 , 12 ]. Arnason et al [ 13 ] have shown that the anthropometrical profile of the soccer players has been associated with measures of match-related performance, and reported that teams with the highest fitness levels and the lowest percentage of body fat (%BF) had a higher league ranking.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of individuals’ linear dimensions, body diameters, body mass, and skinfolds, which are considered the key components of the somatic build profile of an elite player, have been monitored [ 6 , 9 ]. These measurements are critical in selecting players for each position on the court [ 10 , 11 , 12 ]. Arnason et al [ 13 ] have shown that the anthropometrical profile of the soccer players has been associated with measures of match-related performance, and reported that teams with the highest fitness levels and the lowest percentage of body fat (%BF) had a higher league ranking.…”
Section: Introductionmentioning
confidence: 99%
“…En consecuencia, el grado de entrenamiento de fuerza, puede inducir aumentos sustanciales en el mismo (Hickson et al, 1980). Por otra parte, al parecer un IMC y porcentaje de grasa corporal aumentado tendrían un efecto negativo en la capacidad cardiorrespiratoria (Cavia et al, 2019). Los valores de VO2 máx reportados en esta investigación están bajo los niveles requeridos para el futbol.…”
Section: Discussionunclassified
“…Among the studies, which necessitate that the physical participation of individuals like balance, which may affect the results, the studies assessing balance are important. When other studies conducted in the fields of running, swimming and other sports that require balance-level performance were examined, many body anthropometric parameters were taken into account [7,[37][38][39]. It was found that there are limited studies especially examining the relations between balance and foot and body anthropometric measurements [40,41].…”
Section: Discussionmentioning
confidence: 99%